This is for my trig class and the directions say to use the fundamental trigonometric identities to simplify the expression. Please help!

cos^2xcot^2+cos^2x

= cos^2x(cot^2x+1)

= cos^2x csc^2x

= cot^2x <==Answer

Tutors, please sign in to answer this question.

Scottsdale, AZ

cos^2xcot^2+cos^2x

= cos^2x(cot^2x+1)

= cos^2x csc^2x

= cot^2x <==Answer

Yamil V.

Professor at Top University, Politics, Statistics and Programming

New York, NY

5.0
(49 ratings)

Rachel K.

Princeton '13 Math & Computer Science Tutor

New York, NY

5.0
(60 ratings)

- Simplify 241
- Math Help 4334
- Algebra 4176
- Algebra 1 3403
- Algebra 2 2930
- Fractions 520
- Math 7552
- Expressions 99
- Math Help For College 1235
- Algebra Help 901